2018
DOI: 10.1111/jre.12623
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis, periodontal inflammation, and mild cognitive impairment: A 5‐year cohort study

Abstract: Background and Objectives Identification of modifiable factors for mild cognitive impairment (MCI) is important since individuals with MCI are at a high risk of dementia and disability. Previous studies have suggested a potential association between periodontitis and cognitive impairment, but the results remain inconclusive. We designed a 5‐year longitudinal study to explore the association between MCI and periodontitis and periodontal inflammation in older adults. Methods This study included 179 community‐dwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(116 citation statements)
references
References 42 publications
6
109
1
Order By: Relevance
“…Several researchers have investigated the association between cognitive impairment and oral health status, with particular attention to chronic periodontitis; the direction of this association needs to be clarified [11,13,[40][41][42][43][44][45][46]. Chen et al have demonstrated that periodontitis increased the risk of AD 1.7-fold after 10 years [42].…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have investigated the association between cognitive impairment and oral health status, with particular attention to chronic periodontitis; the direction of this association needs to be clarified [11,13,[40][41][42][43][44][45][46]. Chen et al have demonstrated that periodontitis increased the risk of AD 1.7-fold after 10 years [42].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Individuals with cognitive impairment are one subgroup of the older population that is at particularly high risk of poor oral health, including those with mild cognitive impairment and mild dementia. 3,4 Evidence shows that individuals with cognitive impairment have more oral plaque, more severe periodontal disease, more caries, and fewer teeth than cognitively intact older adults. 2,[5][6][7] Research shows that inadequate oral hygiene practices primarily contribute to poor oral health for individuals with cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…A constant challenge when conducting any systematic reviews of periodontal disease are the different case definitions used as they can influence overall estimates. The cohort study by Iwasaki and colleagues (26) included in this review is a prime example. They assessed the association between periodontitis and cognitive impairment across both the European Workshop in Periodontology (where 'severe' periodontitis was associated with an adjusted OR 3.58 (95% CI 1.45-8.87)) and the Centres for Disease Control and Prevention and American Academy of Periodontology definition of 'severe' periodontitis where the adjusted OR was 2.61 (95% CI 1.08-6.28).…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive summaries of 23 included articles published between 1994 and 2018, are chronologically presented in (Supplement Tables 1 and 2) [14,. The studies were conducted in four continents including Europe, North America, South America and Asia (Supplement Tables 1 & 2) [14,22,23,[26][27][28][29][30][31][32][33][34][35][38][39][40][41][42][43][44][45]. The number of participants in each study ranged from 42 in the study by Ship and Puckett to 27,963 in the study by Chen [14,38].…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation